INDIGENOUS PEOPLES’ RIGHTS OVER NATURAL RESOURCES: AN ANALYSIS OF HOST COMMUNITIES RIGHTS IN NIGERIA - Amah Emmanuel Ibiam; Hemen Philip Faga (Lampung Journal of International Law, 2021)
Many States are engulfed in crises over natural resources in the form of claims and counterclaims over who should exercise legal authority over the resources located within the state territory. In Nigeria, the agitation over control of natural resources has led to militancy and rebellion against the federal government and multinational oil companies. The debate on who should control and manage natural oil resources in Nigeria exists at the local community level, the federating states level, and the federal government level. This paper x-rayed the varying contentions of these agitations from an international law perspective. It adopted the doctrinal method to explore international human rights instruments and other legal and non-legal sources to realize the result and arrive at persuasive conclusions. The paper concluded that although international law guarantees states’ exercise of sovereign rights over their natural resources, it safeguards the right of indigenous peoples and communities to manage the natural resources found within their ancestral lands to deepen their economic and social development. It also concluded that the Niger Delta indigenous peoples and oil-producing communities are entitled to exercise some measure of control and management of the processes of exploitation of the natural resources found within their lands. The paper calls on the Nigerian government to fast-track legal and policy reforms to resource rights to indigenous host communities of natural resources in Nigeria.